Cadmium stimulated cooperation between bacterial endophytes and plant intrinsic detoxification mechanism in Lonicera japonica thunb. (June 2023) - Xie, Mengdi; Gao, Xiaoyu; Zhang, Saiwei; Fu, Xiaohua; Le, Yiquan; Wang, Lei
Abstract: Due to the intimate association between plant physiology and metabolism, the internal colonizing microbe (endophytes) community must be adjusted to support plant productivity in response to cell damage in plants under stress. However, how endophytes coordinate their activities with plant intrinsic mechanisms such as antioxidative systems and detoxification pathways during Cd accumulation remains unknown. In this hydroponic pot study, we investigated how exposure of Lonicera japonica. thunb. to different levels of Cd (0.5, 2.5, 5, 10, and 20 mg kg −1 ) affected plant growth, metabolic pathways, and endophyte community structure and function. Although Cd accumulation increased at 5 mg kg −1 Cd, the biomass and height of L. japonica increased in association with elevated endophyte-involved plant detoxification activities. Endophytes, such as Sphingomonas, Klenkia, and Modestobacter, expressed major antioxidative regulators (superoxide dismutase and ascorbate acid) to detoxify Cd in L. japonica . Furthermore, L. japonica and its endophytes synergistically regulated the toxic effects of Cd accumulation via multiple plant metabolic defensive pathways to increase resistance to metal-induced stress. Graphical abstract: Image 1 Highlights: Microbial structure of the endophytes in L. japonica varied under different Cd stress. The hormesis pattern in L. japonica has the same trend with endophytes biodiversity change. Endophytes cooperate mostly with SOD and AsA to reduce oxidative damage by Cd. Endophytes may initiate metabolisms, membrane transport, signal transduction, and immune to detoxify Cd.